2011
DOI: 10.1029/2010jb000846
|View full text |Cite
|
Sign up to set email alerts
|

Subcritical crack growth in rocks under shear loading

Abstract: [1] In this study, the subcritical crack growth parameters for Coconino sandstone under modes II and III loading were determined experimentally by using the constant stress rate test. We extend the constant stress rate test technique to modes II and III subcritical crack growth in rocks. The experimental results of the modes II and III tests, combined with mode I results published elsewhere, show that the values of the modes I, II, and III subcritical crack growth parameters are very similar to each other reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…The general form of the growth law in the subcritical regime is still an issue. Most of the experimental data on rock samples have been obtained for mode I [ Atkinson , ], and only a few for modes II and III [ Ko and Kemeny , ] with results consistent with mode I. The main fitting or theoretical models are either power law or exponential model.…”
Section: The Complete Model Of Fracture Formation: Nucleation Growth and Arrestmentioning
confidence: 99%
See 1 more Smart Citation
“…The general form of the growth law in the subcritical regime is still an issue. Most of the experimental data on rock samples have been obtained for mode I [ Atkinson , ], and only a few for modes II and III [ Ko and Kemeny , ] with results consistent with mode I. The main fitting or theoretical models are either power law or exponential model.…”
Section: The Complete Model Of Fracture Formation: Nucleation Growth and Arrestmentioning
confidence: 99%
“…If power laws and exponential functions have been found to adequately fit the length distributions of geological faults [ Bonnet et al ., ; Korvin , ], the parameters retrieved from fault length distributions are totally inconsistent with those deduced from fracturing experimental data. The subcritical growth index of the Charles' law was found to be larger than 30 [ Atkinson , ; Ko and Kemeny , ], entailing exponents a larger than 15, while the power‐law length exponents a of faults are rarely larger than 4 [ Bonnet et al ., ]. It is even worst for exponential fits, where atomic scale processes are invoked for experimental data [ Darot and Gueguen , ], while the length scale of fault length distributions are meter to kilometer scales.…”
Section: The Complete Model Of Fracture Formation: Nucleation Growth and Arrestmentioning
confidence: 99%
“…Sano et al [9] reported that the influence of stress rate on the uniaxial compressive strength can be expressed as the 1/(n+1) th power of the loading rate. Similarly, according to the subcritical crack growth theory [10], the fracture strength is directly proportionate to the 1/(n+1) th power of the loading rate, where the parameter n represents the stress corrosion index, which is related to the time dependence of rocks. Many researchers have reported that the strength of rocks increases slightly when the loading rate increases under static and quasi-static loading [11][12][13][14][15][16].…”
Section: H-o-h + [≡Si-o-si≡] ↔ 2[≡si-oh]mentioning
confidence: 99%
“…The aim of this study is to simulate the feasibility of the development of a saturated orthogonal fracture network under one constant remote stress regime, using a relation between LEFM and sub critical crack growth, which is used in several other modelling studies (Ko and Kemeny 2011;Olson 2007;Pollard and Segall 1987;Shen and Rinne 2007). We will focus on how an orthogonal fracture network shapes and is shaped by the regional applied effective tensile stresses, available strain energies and material conditions, and compare how the saturated geometries correlate to published field studies.…”
Section: ′L Xmentioning
confidence: 99%
“…(4) and is used in multiple lab an modelling studies describing SCCG (Atkinson 1984;Ko and Kemeny 2011;Nara et al 2012;Olson et al 2009;Shen and Rinne 2007): where v is theoretical sub critical growth rate (m/s), v max is the maximum crack propagation rate, K I(tip) is the stress intensity on the crack tip, K Ic is the mode I fracture toughness (material property) and n is the sub critical crack growth index. We assume that K Ic can be related to the tensile rock strength and an initial crack length ( K Ic = YT 0 √ a initial , where a initial = 0.0125 m), and the magnitudes of n and v max are set to 35 and 100 (m/s), respectively, which is similar to other modelling studies (Ko and Kemeny 2011;Olson et al 2007Olson et al , 2009Rijken 2005;Shen and Rinne 2007). The implemented SCCG approach states that low local tensile stresses result in a low fracture opening, which results in low stress intensities on the crack tip and therefore low calculated fracture propagation velocities.…”
Section: From Local Effective Stresses To a Theoretical Sub Critical mentioning
confidence: 99%